Measurement invariance between the English and German versions of the Informal Workplace Learning scale - dos Santos, Anne Francis (East Carolina University, 2022)
Training efforts in organizations are often quite limited. Thus, finding ways to promote informal learning in the workplace is of key importance for employee development in organizations wishing to remain competitive. Decius et al. (2019) recently developed and validated a 24-item scale measuring informal learning in the workplace. The development of this scale was based on the dynamic model of informal learning (Tannenbaum, Beard, McNall, & Salas, 2010) which is a comprehensive model of informal learning encompassing intent to learn, experience/action, feedback, and reflection. The goal of this study was to conduct a multiple group confirmatory factor analysis (MG-CFA) comparing validated samples from Germany (in the German language) to each other and to a sample collected in the US using the English version of the scale. Overall, strong measurement invariance was found; thus, the English version of the scale can be said to be measuring the same underlying construct as is the validated scale in the German language. Subsequently, results suggest that the English version of the scale can be used in research to learn more about antecedents and outcomes of informal learning in the workplace.
Keywords: informal workplace learning; scale validation; multiple-group confirmatory factor analysis; measurement invariance; Employees--Training of; Occupational training; English language; German language